1990
DOI: 10.1002/jcp.1041440308
|View full text |Cite
|
Sign up to set email alerts
|

Plasminogen activator inhibitor type‐2 Is a major protein induced in human fibroblasts and SK‐MEL‐109 melanoma cells by tumor necrosis factor

Abstract: Tumor necrosis factor (TNF) induces the synthesis of two proteins of Mr 42 and 36 kDa in human fibroblasts and SK-MEL-109 melanoma cells. To identify these proteins, a lambda gt10 cDNA library was prepared from the mRNA of TNF-treated SK-MEL-109 cells. By screening this library, we found a cDNA that preferentially hybridized to TNF-induced RNA. Hybrid-selected mRNA was translated into a protein of 42 kDa; cDNA sequence analysis followed by a comparison with other known protein sequences identified this protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 43 publications
1
26
0
Order By: Relevance
“…In such situations intracellular PAI-2 could be polymerized. Tumor-necrosis factor, capable of inducing apoptosis (Laster et al, 1988), also causes an increased expression of PAI-2 (Pytel et al, 1990) which appears to antagonize the cytolytic effect of the cytokine (Kumar and Baglioni, 1991). Increased PAI-2 expression also occurs in aged fibroblasts (Kumar et al, 1992), and in malignant cells transformed by the rus and src oncogenes (Cohen et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In such situations intracellular PAI-2 could be polymerized. Tumor-necrosis factor, capable of inducing apoptosis (Laster et al, 1988), also causes an increased expression of PAI-2 (Pytel et al, 1990) which appears to antagonize the cytolytic effect of the cytokine (Kumar and Baglioni, 1991). Increased PAI-2 expression also occurs in aged fibroblasts (Kumar et al, 1992), and in malignant cells transformed by the rus and src oncogenes (Cohen et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…try, University of Aarhus, DK-8000 Aarhus C, Denmark cells, fibroblasts and melanoma cells (Scarpati and Sadler, 1989;Pytel et al, 1990;Johnson and Baglioni, 1990). It is present in the blood of pregnant women (Astedt et al, 1987) and in patients suffering from myeloid leukemia (Scherrer et al, 1991).…”
mentioning
confidence: 99%
“…The discrepancy in the degree of mRNA production was suggestive of inducible stabilization of PAI-2 mRNA under these conditions. Subsequent studies have shown that the rate of PAI-2 mRNA decay can indeed be reduced by phorbol ester (15) and dioxin (16) or increased by dexamethasone (17).…”
mentioning
confidence: 99%
“…Indeed, PAL2 is the most TNF-inducible protein observed in fibroblasts (Pytel et al, 1990;Beresini et al, 1988). In this report, we demonstrate that the PAI-2 gene promoter possesses two repressor regions ; one located distally between positions -1859 and -11 00, and one located proximally within a 40-bp region between positions -259 and -219.…”
mentioning
confidence: 99%